Central Auditory Nervous System Stimulation through the Cochlear Implant Use and Its Behavioral Impacts: A Longitudinal Study of Case Series - Cavalcanti, Marina Isabel; Silva, Liliane Aparecida Fagundes; Goffi Gomez, Maria Valéria Schmidt; Koji, Tsuji Robinson; Bento, Ricardo Ferreira; Martinho de Carvalho, Ana Cláudia; Gentile, Matas Carla (Case Reports in Otolaryngology, 2021)
The purpose of this study was to investigate, over a period of five years, the cortical maturation of the central auditory pathways and its impacts on the auditory and oral language development of children with effective use and without effective use of a Cochlear Implant (CI). A case series study was conducted with seven children who were CI users and seven children with normal hearing, with age- and gender-matched to CI users. The assessment was performed by long-latency auditory evoked potentials and auditory and oral language behavioral protocols. The results pronounced P1 latency decrease in all CI users in the first nine months. Over five years, five children with effective CI use presented decrease or stabilization of P1 latency and a gradual development of auditory and oral language skills, although, for most of the children, the electrophysiological and behavior results remained poor than their hearing peers’ results. Two children who stopped the effective use of CI after the first year of activation had worsened auditory and oral language behavioral skills and presented increased P1 latency. A negative correlation was observed between behavioral measures and the P1 latency, the P1 component being considered an important clinical resource capable of measuring the cortical maturation and the behavioral evolution.